Problema Dualisme Personalitas Hukum Pada Anggota Komponen Cadangan Indonesia - Suwartono, Rahadian Diffaul Barraq (Fakultas Hukum Universitas Islam Indonesia, 2025)
The Reserve Component, a non-regular military unit in Indonesia, is envisioned as a complement to the Indonesian National Armed Forces (TNI) in national defense efforts. The establishment of the Reserve Component in Indonesia is based on the dual legal personality of its members. This dualism manifests in the legal personality status of Reserve Component members, which can shift between military and civilian statuses in an unstable manner. This dual legal personality of Reserve Component members apparently presents a looming derivative risk. This article aims to analyze the reasons behind the formulation and the problems faced by the dual legal personality of Reserve Component members. This research has never been conducted in Indonesia. This article utilises a socio-legal study that combines legal and civil-military approaches in social science studies. The legal approaches used as research tools in this article are statutory and conceptual. This article finds that the Reserve Component concept is based on the Total War doctrine, which is translated into the Total Defense System policy in Indonesia. The existence of this doctrine forms the basis for the formulation of the Reserve Component, which must have dual legal personality, making this dualism impossible to eliminate. In fact, the dual legal personality of Reserve Component members has resulted in several issues, including but not limited to ambiguity in court proceedings, civil-military friction, and even issues regarding the neutrality of Reserve Component personnel in general elections.